2014
DOI: 10.1097/gox.0000000000000019
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the Use of Therapy following Distal Radius Fractures in the United States

Abstract: Background:Distal radius fractures (DRFs) are one of the most common injuries among the elderly, resulting in significant expense and disability. The specific aims of this study are (1) to examine rates of therapy following DRFs and (2) to identify those factors that influence utilization of therapy and time span between DRF treatment and therapy among a national cohort of elderly patients.Methods:We examined national use of physical and occupational therapy among all Medicare beneficiaries who suffered DRFs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Consequently, variation in care has been of great interest for researchers investigating ways to help promote high-quality care. 36,37 In our study, we found geographic variation in the ED utilization for DRF-related and potentially preventable pain diagnoses 30 days after treatment. Our findings corroborated with other research on variation in ED admission rates across different United States regions.…”
Section: Resultsmentioning
confidence: 55%
“…Consequently, variation in care has been of great interest for researchers investigating ways to help promote high-quality care. 36,37 In our study, we found geographic variation in the ED utilization for DRF-related and potentially preventable pain diagnoses 30 days after treatment. Our findings corroborated with other research on variation in ED admission rates across different United States regions.…”
Section: Resultsmentioning
confidence: 55%
“…Finally, patients who underwent operative intervention were more likely to receive post-acute rehabilitation, suggesting that treatment type and fracture severity is correlated with the time needed to return to independent functioning. (4)…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we excluded all enrollees of Medicare Advantage plans or with bone-malignancy related claims. (4, 5,17) To capture incidence DRF cases, we only included patients who were treated operatively (open reduction and internal fixation (ORIF), external fixation, or percutaneous pinning) or non-operatively (closed reduction, casting or splinting) within 14 days following the earliest diagnosis of DRF. (Appendix 2)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Higher SES has also been found to be associated with greater use of postoperative therapy such as physical or occupational therapy that would presumably be associated with better patient outcomes. 34 A review of claims and regional data revealed that patients of high (OR, 1.57; 95% CI, 1.46-1.70) or medium (OR, 1.22; 95% CI, 1.12-1.32) SES were more likely to receive therapy compared with patients of lower SES.…”
Section: Incomementioning
confidence: 99%